One thing goats don't like - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
It is common knowledge that goats are not really fussy eaters. This trait can cause a lot of damage to trees, including productive ones like fruit trees. Manure slurry applied to the trunk gives off a repulsive ammonia smell, which proves an easy...